The relationship between vitamin D deficiency and gestational diabetes mellitus - Marzieh Lotfalizadeh; Negar Ramezanpour; Kosar Deldar; Mansoureh Mohammadnezhad (Mashhad University of Medical Sciences, 2022)
Introduction: Gestational diabetes mellitus (GDM) is the most common problem in pregnancy and about 1-20% of pregnant women have GDM. Therefore, it is significantly importance to prevent and treat GDM. Numerous researchers have explored the possible risk factors of GDM. Vitamin D deficiency is one of these risk factors that has ambiguous results, therefore, this study was performed with aim to investigate the relationship between serum vitamin D levels and gestational diabetes.Methods: This prospective study was conducted in 2017-2018 on pregnant women aged 15-40 years with inclusion criteria who referred to health services centers in Mashhad in first trimester of pregnancy for prenatal care. Data related to age and BMI was recorded. Then, 5 cc of blood was taken from all participants to measure 25-hydroxyvitamin D3. All participants underwent the Oral Glucose Tolerance Test (OGTT) at 24-28 weeks of gestation. Data were analyzed by SPSS software (version 16) and Independent t-test, Mann-Whitney, Chi-square and Fisher's exact test. P<0.05 was considered statistically significantResults: From 449 participants, 320 (71.2%) had lower than normal levels of vitamin D that 68 (15.1%) of participants suffered from vitamin D deficiency and 252 (56.1%) suffered from vitamin D insufficiency. In addition, 7 participants (1.6%) had the higher levels of vitamin D and 122 (27%) had normal vitamin D. Among the subjects, 41 (9.1%) developed gestational diabetes. The median of vitamin D levels within non-diabetic group was 22 ng/cc and 18 ng/cc for diabetic group, although there was difference, but the difference was not significant between the two groups (p=0.555).Conclusion: Although vitamin D level was lower in GDM patients, but there was no relationship between vitamin D and gestational diabetes and both groups had vitamin D level lower than normal range.